An Analytical Study of Consumer Attitudes towards Chinese Mobile Phone in India- with Special Reference to Rajkot City - Ahmed Mahdi Abdulkareem; Alok Kumar Chakrawal (Newinera Publisher, 2021)
The main objective behind this study is to know the attitude of the persons towards Chinese mobile phone with reference to public stay in Rajkot city. The researcher collected data from the primary source and secondary sources. Primary data collected through a structured questionnaire that close and open-ended and secondary data collected from the market on the basis of website, newspaper, and other secondary sources. The researcher has the main objective behind the study is to measures consumer attitude towards Chinese products and to find the relation between gender with respect to spending purchasing of Chinese mobile phones and in last to find the significant relation between monthly income with respect to opinion of the respondent towards Chinese mobile phones are cheaper than other brands. The researcher tested his hypothesis on the basis of some statistical tools which are percentage analysis, weighted average, and chi-square test. The researcher found out through this study up to 69% male respondents and 31% female respondents in the study, more than 80% of respondents are using Chinese mobile phone in Rajkot city. The majority of 91% of the respondents are agreeing with those Chinese mobile phones are cheaper than other mobile phones.